The Evolution Logic and Implications of Clinical Medical Education Reform in the United States from the Perspective of Medical-Education Collaboration - Yan GAO; Ana XIE; Jianlin HOU; You YOU; Weimin WANG (Yixue yu zhexue)
Since the early 20th century, clinical medical education in the United States has undergone three major reforms, each of which has profoundly influenced the global landscape and development trajectory of medical education. Viewed through the lens of medical-education collaboration, these reforms exhibit a clear evolutionary logic in terms of reform goals, institutional cooperation, and curriculum design. The reform goals have shifted from cultivating doctors' scientific thinking to competency orientation, institutional cooperation has evolved from institutionalized foundation to ecological collaboration, and curriculum design has progressed from segmented practice to deep integration. These developments have gradually established a medical education collaboration system with "dynamic goal-setting, ecosystem-based cooperation, and clinically-oriented curricula", promoting a deep coupling of the medical education system and the healthcare system. China can learn from its reform experience, establish a dynamic response mechanism for educational goals, build a cross-sectoral collaborative governance structure, and strengthen the clinical orientation and integration of medical curricula.